A study to assess the effect of supplementary nutrition on nutritional status of preschool children in selected Anganwadis, Bengaluru South - Sambhu Viswanath; P M Thressiamma; M B Sunil (Wolters Kluwer Medknow Publications, 2021)
Background of the Study: Protein energy malnutrition has been identified as a major health and nutrition problem in India. Hence, the investigator felt the need to evaluate the effectiveness of nutritional supplement among preschool children in selected Anganwadis, Bengaluru. Materials and Methods: Using purposive sampling technique, a total of 60 samples were selected with 30 in experimental and 30 in control group. Quasi-experimental design with pretest nutritional assessment and posttest nutritional assessment with control design is used. Results: The prereading mean weight score was 11.49 and the postreading score increased to 12.28. Similarly, the prereading mean score of height 94.32 increased to a mean score of 94.52 in posttest. While considering the head circumference of the preschool children, the pretest mean score of 47.82 changed to 48.03 during the posttest. During the pretest, the mean reading of mid-arm circumference was 14.67, which then increased to a mean value of 14.80 during the posttest. The chest circumference of the children was 50.85 during the pretest which then increased to 51.01 during the posttest. Thus, an overall improvement had occurred in the anthropometric measurements of preschool children even though statistically, it is not significant. Conclusion: The overall findings of the study revealed that there was a marked improvement in the anthropometric measurements of preschool children. Hence, it can be concluded that the nutritional supplement was effective in improving the nutritional status of the children.